2020
DOI: 10.3390/electronics9111877
|View full text |Cite
|
Sign up to set email alerts
|

Overwater Image Dehazing via Cycle-Consistent Generative Adversarial Network

Abstract: In contrast to images taken on land scenes, images taken over water are more prone to degradation due to the influence of the haze. However, existing image dehazing methods are mainly developed for land-scene images and perform poorly when applied to overwater images. To address this problem, we collect the first overwater image dehazing dataset and propose a Generative Adversial Network (GAN)-based method called OverWater Image Dehazing GAN (OWI-DehazeGAN). Due to the difficulties of collecting paired hazy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In order to improve the image quality and diversity generated by GANs, the current research on GANs almost stays in the spatial domain. For example, CycleGAN++ [30] improves the phenomenon that the CycleGAN [13] generator may hide some features in the input image and restore them at the time of output, eliminating the circular structure of CycleGAN, removing the loss of cyclic consistency and adding the loss of classification; StyleGAN2 [31] improved the problem that the image generated by StyleGAN [14] may have obvious water droplets. These are improvements to some problems existing in the airspace of the images generated by the existing GANs Although there are also improvements for frequency-domain characteristics, the optimization methods are usually different for different frequency-domain characteristics.…”
Section: High-order Optimization Of Image Generationmentioning
confidence: 99%
“…In order to improve the image quality and diversity generated by GANs, the current research on GANs almost stays in the spatial domain. For example, CycleGAN++ [30] improves the phenomenon that the CycleGAN [13] generator may hide some features in the input image and restore them at the time of output, eliminating the circular structure of CycleGAN, removing the loss of cyclic consistency and adding the loss of classification; StyleGAN2 [31] improved the problem that the image generated by StyleGAN [14] may have obvious water droplets. These are improvements to some problems existing in the airspace of the images generated by the existing GANs Although there are also improvements for frequency-domain characteristics, the optimization methods are usually different for different frequency-domain characteristics.…”
Section: High-order Optimization Of Image Generationmentioning
confidence: 99%
“…In 2023, Zhang et al, [23] suggested an enhanced cycle-consistent attacker network-based imagedefogging system. Then, to enhance the network's capacity for feature extraction, the self-recognition module and the multi-scale feature fusion module for atrous convolution are built on the conventional Cycle GAN network.…”
Section: Literature Surveymentioning
confidence: 99%
“…This dynamic nature poses challenges for image restoration, as algorithms must adapt to evolving weather conditions. Thus, effective image restoration techniques tailored to the unique characteristics of maritime environments are essential for ensuring safe and efficient maritime activities (Zheng et al, 2020). This raises a question: how to better help image restoration in adapting to the complex and ever-changing maritime scenes under adverse weather conditions?…”
mentioning
confidence: 99%